2022
DOI: 10.2147/copd.s383914
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Hospital Pharmacist Interventions for COPD Patients: A Systematic Literature Review and Logic Model

Abstract: Purpose This review aimed to summarize empirical evidence about pharmacist-led interventions for chronic obstructive pulmonary disease (COPD) patients in hospital settings and to identify the components of a logic model (including input, interventions, output, outcome and contextual factors) to inform the development of hospital pharmacist’s role in COPD management. Methods A systematic review of literature retrieved from four English databases (PubMed, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Hospital pharmacists have taken advantage of cross-departmental and multidisciplinary collaboration to educate and manage the disease status of patients,27 use remote medication procedures to monitor and guide patients’ medication,8 and conduct cognitive screening for elderly patients with metabolic diseases to eliminate hidden dangers of medication 29. Different levels of graded pharmaceutical care measures are implemented at different stages of the disease,30 which can identify and intervene in drug-related problems in a timely manner in the treatment of COPD and other diseases 31. In addition, it enables correct understanding of the connotation of pharmacy services, forming good values, encouraging innovative strategies such as personalised pharmaceutical care to improve patient satisfaction and improve prognosis 32–34…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital pharmacists have taken advantage of cross-departmental and multidisciplinary collaboration to educate and manage the disease status of patients,27 use remote medication procedures to monitor and guide patients’ medication,8 and conduct cognitive screening for elderly patients with metabolic diseases to eliminate hidden dangers of medication 29. Different levels of graded pharmaceutical care measures are implemented at different stages of the disease,30 which can identify and intervene in drug-related problems in a timely manner in the treatment of COPD and other diseases 31. In addition, it enables correct understanding of the connotation of pharmacy services, forming good values, encouraging innovative strategies such as personalised pharmaceutical care to improve patient satisfaction and improve prognosis 32–34…”
Section: Resultsmentioning
confidence: 99%
“…29 Different levels of graded pharmaceutical care measures are implemented at different stages of the disease, 30 which can identify and intervene in drug-related problems in a timely manner in the treatment of COPD and other diseases. 31 In addition, it enables correct understanding of the connotation of pharmacy services, forming good values, encouraging innovative strategies such as personalised pharmaceutical care to improve patient satisfaction and improve prognosis. [32][33][34]…”
Section: Analysis Of Abstractmentioning
confidence: 99%
“…The design of the questionnaire was based on a previous literature review on pharmacist intervention for pediatric asthma 20 . The questionnaire consisted of 5 sections, including participant quali cation con rmation (1 question), demographics (9 questions), caregivers' perception of asthma-related knowledge (19 questions), the burden on caregivers due to pediatric asthma (5 questions), and their needs of pharmaceutical care provided by community pharmacists (12 questions).…”
Section: Questionnaire Designmentioning
confidence: 99%
“…10,11 Only one systematic review with a randomized controlled trial study reported that the pharmacist's role in the hospital has contributed to various aspects of COPD management, both inpatient and outpatient. 13 Therefore, this systematic review aimed to evaluate specifically the impact of providing education on the technique of using inhalers by hospital pharmacists in improving the quality of life of inpatient and outpatient COPD patients. The purpose of selecting inpatients and outpatients is to assist patients in enhancing treatment safety, patient outcomes, and drug quality over time and to prevent readmissions in inpatient settings.…”
Section: Systematic Reviewmentioning
confidence: 99%